Electroproduction of Hypernuclei - Denisova Daria; Bydžovský Petr; Veselý Petr; Skoupil Dalibor (EPJ Web of Conferences, 2024)
Abstract. The electroproduction of hypernuclei initiates a captivating domain of study, offering great insights into the characteristics of composite nucleon-hyperon systems. This inquiry assumes prime significance as it displays critical features of nuclear matter structure and tests the interactions between hyperons and nucleons. In this paper, we unveil the distorted-wave impulse approximation (DWIA) approach, aimed at explaining the cross sections in electroproduc-tion of Λ-hypernuclei. Our investigation examines how various model assumptions affect the results we get. We focus on two important factors: influence of the proton Fermi motion and description of the various models of nuclear and hypernuclear structure.